Identification of key genes and enzymes contributing to nutrition conversion of Torreya grandis nuts during post-ripening process. (1st August 2022) - Song, Lili; Meng, Xuecheng; Yang, Lei; Ma, Zhenmin; Zhou, Minying; Yu, Chenliang; Zhang, Zuying; Yu, Weiwu; Wu, Jiasheng; Lou, Heqiang
Highlights: Gene expression profiles were compared in different temperature and humidity treated seeds. The nutrition conversion pathway of T. grandis was proposed firstly. The key factors promoting nutrition conversion during post-ripening were identified. Abstract: The seeds of Torreya grandis are necessary to go through a ripening process, which eventually leads to nutrition conversion and the production of edible nuts. However, the molecular basis of nutrition conversion remains unclear. Here, transcriptome sequencing was performed on seeds treated with different temperature and humidity. A total of 881 unigenes related to nutrition conversion were identified. The correlations between nutrient content and gene expression suggested that sucrose phosphate synthase (SPS), dihydrolipoyllysine-residue succinyltransferase component of 2-oxoglutarate dehydrogenase complex (DLST), glycerol-3-phosphate acyltransferase (GPAT) and Pyruvate kinase (PK) may play key roles in nutrition conversion. Transient over-expression of TgDLST, TgPK and TgGPAT in tobacco leaves promoted nutritional conversion. Moreover, enzyme activity analysis indicated that diacylglycerol acyltransferase (DGAT) and pyruvate dehydrogenase (PDH) activities may also accelerate the nutritional conversion. This study uncovers the molecular basis of nutrition conversion in T. grandis seeds, which critical for shortening the time of nutrition conversion.